Kritik Hermeneutik dan Kontekstualisasi Ayat-Ayat Hukum - Yusep Rafiqi (AHKAM : Jurnal Ilmu Syariah, 2017)
Hermeneutics is often suspected as 'not from the Islamic treasury'. Although the topic of interpretation has been introduced by Aristotle in“ On Interpretation,” Hermeneutics became an independent subject in the science of philosophy in the seventeenth century mainly related to theinterpretation of texts and literary works. Another suspicion of the presence of Hermeneutics in Islamic treasures is the interpretive methodology that makes reconstructed texts as a center of study. It may lead the reader toother dimensions outside the convention. Beyond the pros and cons of thestudy of hermeneutics, this article explores the importance of hermeneutic methods and the contextualization of legal verses in the Qur'an to meet the needs of dynamic societies. DOI: 10.15408/ajis.v17i1.6088